Urban and architectural design for the young mind: An ecological investigation of the relationship between urban form and adolescent mental health - Buttazzoni, Adrian (University of Waterloo, 2022)
Around 50% of lifetime mental illnesses begin at or prior to the age of 14 years old—or roughly halfway through adolescence (10-19 years old)—with contemporary trends from multiple geographical and cultural contexts indicating upward trends in various conditions (e.g., anxiety, depression). Concomitant to these developments in adolescent mental health trends, the global population continues to urbanize portending that a higher proportion of adolescents will experience these critical developmental years in such environs. Together the coalescing of these health and migration trends suggests that the role and influence of urban environments in the mental health and well-being of adolescents will be especially important in the coming years. Common paths of research regarding the mental health of younger populations, however, have tended to focus on individual psychosocial issues and physiological factors, subsequently leaving comparatively little knowledge about the specific urban design influences of adolescent mental health and well-being. Further research investigating more robust associations between precise urban environment design characteristics and adolescent mental health outcomes, along with a greater diversity of methods, is warranted for both advancing scholarship on this topic and informing professional practice in relevant fields such as urban planning and public health. This dissertation provides an exploratory mixed methods evaluation of the relationships between specific urban and architectural designs and adolescent mental health indicators (i.e., emotional responses). Guiding this evaluation is the overarching question: “What is the nature of the relationship between specific urban built and natural design concepts and adolescent mental health indicators (i.e., emotional responses)?” Overall, seven chapters comprise this dissertation with five featuring as integrated articles. After the introduction (Chapter 1), the first of the integrated articles (Chapter 2) reviews and synthesizes literature from across the fields of planning and public health, as well as the emerging transdisciplinary area of neurourbanism. The resulting syntheses of this review highlight how planning and public health have traditionally understood the relationships between health and urban environments, and subsequently how these relationships are being investigated using contemporary methods. From this background, the reviewed literature is then specifically applied to delineate the multilevel nature of the relationship between young people’s mental health and urban environments, and how this topic may be studied and supported through future inter/transdisciplinary research and practice collaborations. To this end, the review offers two novel, socioecological model-based frameworks that include a new fifth level (i.e., the digital level) for both practice and research to consider in future endeavours. Building from the review of the previous chapter and narrowing in more specifically on urban design and adolescent mental health, the following four integrated articles are primary research manuscripts that are framed within the ecological perspective of the Theory of Affordances (ToA). This framing consequently facilitated the development of insights that take into account and explore a variety of influences including social, psychological, physiological, relational, and environmental factors that may be relevant to the relationships under study. Using this approach three separate primary research studies were conducted to explore the relationships between specific urban designs (i.e., pedestrian- and transit-oriented designs (PTOD), cognitive architecture (CA) concepts) and adolescent mental health indicators (i.e., the emotional responses of: positive affect, negative affect, calmness, anxiousness, perceived restorativeness, mental demand). The first primary research integrated article, Chapter 3, submits the results of 23 qualitative go-along interviews that were conducted with adolescents in settings throughout downtown Kitchener, Ontario, Canada. Findings from the qualitative analysis illustrate the considerably different perceptions that adolescents hold regarding a variety of PTODs—for instance, natural versus built enclosure and imageability—and their generally positive perspectives pertaining to the CA concepts examined. The second and third primary research articles, Chapters 4 and 5, present the findings of an online survey featuring a nationally representative sample of 1,500 Canadian adolescents. The former manuscript (i.e., Chapter 4) explores the associations between overall environmental design quality (i.e., areas scored for PTOD quality) and adolescent mental health indicators and finds that, generally, as the aggregated PTOD quality of a setting increased, positive emotional responses also tended to increase while negative responses typically decreased. The latter online survey paper (i.e., Chapter 5) examines associations between specific PTOD concepts (i.e., complexity, enclosure, human scale, imageability, transparency) and adolescent emotional responses. Results from this chapter indicate that the specific design concepts of transparency (increases in positive affect, calmness, and restorativeness), scale (increase in positive affect decrease in negative affect) and complexity (increase in positive affect, decrease in negative affect) may be particularly effectual design concepts for adolescents. Chapter 6, the final integrated article, presents the findings of the EMA survey study which was conducted with 70 adolescent participants also in the downtown area of Kitchener, Ontario, Canada. This study concludes by reiterating the potential of natural forms imageability and enclosure and instances of biophilic architecture (i.e., urban gardens) in environmental design (as noted in Chapter 3), while also suggesting that the potential benefits of PTODs in auto-oriented spaces (e.g., public transit areas) may be offset by a lack of opportunity for adolescents to develop symbolic and stylistic attachments in these settings. Chapter 7 summates the methodological and research contributions of the five integrated articles contained within the dissertation via a triangulation of key shared ideas and points among their collective findings. Contextualized within the ToA, the final chapter’s synthesis suggests two important contributions from this scholarship. First, is that it provides a detailed documentation of the mental health implications of design quality and composition with respect to affording positive social contexts and interaction opportunities, emotionally engaging public spaces, and active use experiences. Discussions of this contribution are expanded to note its implications with respect to adolescent place attachment. And second, this dissertation offers a comprehensive exploratory investigation of the mental health implications of adolescent perceptions of and emotional responses to urban designs which resulted in the identification of trends suggesting a seeming emphasis regarding usage opportunities, safety, distinctiveness, visual richness, and positive affect experiences. The implications of this contribution are connected to better understanding and designing for adolescent place preferences. Future research opportunities are detailed for additional mixed methods studies, environment-based interventions, work with practitioners, and policy analyses.
Keywords: adolescents; built environments; cognitive architecture; ecological momentary assessment; environmental psychology; go-along interviews; health geography; health promotion; mental health; mixed methods; neurourbanism; pedestrian infrastructure; pedestrian- and transit-oriented design; planning; public health; qualitative methods; quantitative methods; Theory of Affordances; urban design; youth